DEFRAGMENTİNG STUDENTS' THİNKİNG STRUCTURE İN SOLVİNG MATHEMATİCAL ARGUMENTS - Nonik Indrawatiningsih; Andika Setyo Budi Lestari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The structure of thinking is a representation of the thought process in the form of a problem-solving flow that is carried out by a person when he resolves a problem. many students make mistakes in solving problems. One way that can be done to overcome these errors is to defragment the structure of thought. This study aims to describe the students’ erroneous thinking structure in solving mathematical argument and the defragmenting efforts. The students of 10th Grade of high school in Pasuruan, East Java, Indonesia, were involved as research subjects. They were selected based on three criteria, namely low, moderate and high level of procedural error. The activity of ‘think out loud’ was used to observe the errors made by students in solving mathematical argument. The data obtained from this activity were codified and later used as a basis to perform the defragmenting process. Based on the findings of this study, it can be concluded that procedural errors in solving mathematical argument are in the form of error in determining the value of x from an equation, modeling an argument, and proving a valid argument. Defragmenting was done using scaffolding approach to improve students' thinking structure in solving mathematical problems